Skrining Status Gizi Remaja Putri dalam Upaya Peningkatan Kesehatan Remaja - Nanda Mirani; Ayunin Syahida (ARDHI : Jurnal Pengabdian Dalam Negri, 2024)
Adolescents are a group aged 10-18 years who need various nutrients. Adolescents need more nutrients, because it is a transition period from childhood to adulthood. Assessment and monitoring of adolescent nutritional status needs to be done to prevent nutritional and health problems in adulthood. This community service was carried out on 11 female adolescents who were willing to undergo nutritional status screening. The activities to be carried out include measuring hemoglobin (Hb) levels, measuring upper arm circumference (LiLA), and providing education about adolescent nutrition. The results of the activity obtained an increase in participant knowledge about nutritional status after being given education, there were 2 participants who had anemia with Hb examination results <12g/dL and there were 3 participants who had LiLa <23.5 cm. Participants already understand and are able to perform Hb examinations using the Easy Touch GCHb tool and LiLA measurements.